2017
DOI: 10.1016/j.drugalcdep.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Toward precision smoking cessation treatment II: Proximal effects of smoking cessation intervention components on putative mechanisms of action

Abstract: Background Understanding how smoking cessation treatments exert their effects can inform treatment development and use. Factorial designs allow researchers to examine whether multiple intervention components affect hypothesized change mechanisms, and whether the affected mechanisms are related to cessation. Methods This is a secondary data analysis of smokers recruited during primary care visits (N=637, 55% women, 87% white) who were motivated to quit. Participants in this fractional factorial experiment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This is possibly because vaping is mimicking aspects of smoking, including positive aspects, in a way that NRT does not . There is little research on self‐efficacy and NRT use post‐quitting, although one study found no significant increase in self‐efficacy with NRT use after the quit attempt . The most recent Cochrane review for relapse prevention found some evidence for extended use of varenicline but not for NRT, although NRT appeared to be useful for those who had quit without support.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly because vaping is mimicking aspects of smoking, including positive aspects, in a way that NRT does not . There is little research on self‐efficacy and NRT use post‐quitting, although one study found no significant increase in self‐efficacy with NRT use after the quit attempt . The most recent Cochrane review for relapse prevention found some evidence for extended use of varenicline but not for NRT, although NRT appeared to be useful for those who had quit without support.…”
Section: Discussionmentioning
confidence: 99%
“…being around others smoking or vaping) and internal cues (positive and negative affect, craving, difficulty concentrating). We have used the internal cue items in previous EMA research [31–33]; many items were adapted from established measures, including the positive and negative affect schedule (PANAS) and the Wisconsin smoking withdrawal scale (WSWS) [34,35]. Expectations of reward from product use were also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…This disjunction between what counseling treatment affects, and what affects abstinence, warrants attention; we essentially replicated this disconnect in a second, more recent study. 16 It is worth considering how different the results have been for research on the mediation of pharmacotherapy effects. Studies have consistently shown that pharmacotherapies reliably and meaningfully reduce major determinants of cessation success: that is, craving and withdrawal symptoms.…”
Section: Counseling Contentmentioning
confidence: 99%